Development of a ground-based radar for scattering measurements - Koo, Voon Chet; Chung, Boon Kuan; Chuah, Hean Teik (IEEE Xplore, 2003)
A ground-based C-band scatterometer system has been constructed at the Multimedia University, Malaysia. This is an inexpensive FM-CW radar that was efficiently constructed from a combination of commercially available components and in-house fabricated circuitry. The system has full polarimetric capability for determining the complete backscattering matrix of a natural target. It will be used to conduct in-situ backscatter measurements on Earth terrain, such as vegetation fields, forests, and soil surfaces. This paper presents the system design and the evaluation results of the scatterometer system. The system was tested at a football field. A metal sphere was used as the calibration target. The backscattering matrices of an 8" trihedral corner reflector and of a 4" x 8" dihedral corner reflector were measured. The dihedral was rotated at different angles to provide different sets of polarimetric data. The results were compared with the theoretical values to verify the effectiveness of the calibration technique. The external calibration and internal calibration procedures, as well as the approach used in measuring the relative phase response, are discussed.